Peran Sarana Angkutan Darat Dalam Upaya Peningkatan Efisiensi Distribusi Ternak Dan Hasil Ternak Sapi Potong Di Indonesia - Winarso, Bambang (Politeknik Negeri Lampung., 2015)
In livestock trading system and cattle product such as meat and other livestock products always involves some businesses that make up the chain of marketing. Tradable commodity that can be distributed right from the producer to the end consumer in the form of live cattle or in the form of livestock product. Distribution activities of livestock and livestock products by land necessarily involves a good means of land transport trains, trucks and other means of land transport. While also involving the various levels of the marketing chain of middlemen village level, large padagang up with retailers. Implementation of the distribution chain between marketing is not just a process of transporting goods. Consistent with the mechanism of the existing business, there will be a new price formation on each node chain path. The longer the chain through which the formation of prices will be higher . Such conditions led to the emergence of the marketing margin distribution on each node marketing chain. The amount of the marketing margin generated between the node is varied, it is largely determined by many things, in addition to the cost of marketing, also the advantage taken by the perpetrator. The study was conducted in East Java and West Java in 2013. Analysis of data using simple cross-tabulation of data derived from primary data and secondary data Keywords: Land Transport, Distribution and Livestock